(untitled) (Eurasian Scientific Herald, 2022)
This article covers the technology of chemical thermal processing. Any iron item can be subjected to rust. There are different ways to clean rust and protect the iron from such interactions. Below we give theoretical information about rust removal and chemical thermal treatment technology from auto parts.